Konstruksi Sosial pada Pernikahan Endogami Lembaga Dakwah Islam Indonesia (LDII) di Kota Banjarbaru - Fahma, Erisa Nur; An'Amta, Dimas Asto Aji (Huma: Jurnal Sosiologi, 2025)
Amid growing social openness, the Islamic organization LDII (Lembaga Dakwah Islam Indonesia) in Banjarbaru continues to uphold endogamous marriage practices. This study aims to explore how such practices are rooted within the organization. Using a qualitative approach with a phenomenological method, the research applies Peter L. Berger and Thomas Luckmann’s theory of social construction as its analytical framework. Data were collected through participant observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model: data collection, reduction, presentation, and conclusion. The findings show that the social construction of endogamous marriage unfolds through three stages: (1) externalization, values are disseminated via religious gatherings, preacher guidance, and forums; (2) objectivation, teachings become institutionalized and reinforced by a Marriage Team, forming an accepted social reality; and (3) internalization, individuals embrace these values as part of their religious and moral identity. Contributing factors include parental influence, preacher roles, adherence to organizational norms, and member interactions, which collectively shape a shared consciousness that sustains the practice across generations. In conclusion, endogamous marriage within LDII functions as a strategic means of preserving organizational identity amid ongoing social change. These findings contribute to studies in the sociology of religion and family, particularly regarding marriage practices in Indonesian religious organizations.